PENDAMPINGAN KELOMPOK TERNAK AYAM UNTUK PEMBUATAN JAMU HERBAL (CARA FERMENTASI) DI DESA URAUR, KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Papilaya, Bercomien Juliet; Horhoruw, W.M.; Rajab, Rajab; Sarfan, Riri (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2024)
Free-range chicken farming is a business that has the potential to meet family needs, and has a large role in supporting the community's economy. Many of these farms are found in rural areas, generally of a traditional nature. Simple housing and simple feeding such as providing kitchen waste. The rest of the chickens themselves have to try to survive and fulfill their food needs in the yard. The negative impact of maintenance like this is low production and damage to yard plants. The main aim of this activity is to maintain livestock health by making and administering herbal medicine/fermented herbal medicine which is made together in groups (demonstration plots). Apart from that, train and motivate farmers to improve the rearing system so that they can develop free-range chicken farming businesses and become providers of chicken seeds. The target of implementing community service activities is a group of village chicken breeders in Uraur village, Kairatu sub-district, who have the will to implement new innovations to increase production and welfare of their families/community as well as for the chicken breeder community in general. The success of this activity is measured by the farmer's attention to chicken farming. Chickens given herbal medicine have better body resistance to disease and extreme environmental influences.